Different Bacterial Communities Involved in Peptide Decomposition between Normoxic and Hypoxic Coastal Waters - Liu, Shuting; Wawrik, Boris; Liu, Zhanfei (Frontiers in Microbiology, 2017)
Proteins and peptides are key components of the labile dissolved organic matter pool in marine environments. Knowing which types of bacteria metabolize peptides can inform the factors that govern peptide decomposition and further carbon and nitrogen remineralization in marine environments. A 13C-labeled tetrapeptide, alanine-valine-phenylalanine-alanine (AVFA), was added to both surface (normoxic) and bottom (hypoxic) seawater from a coastal station in the northern Gulf of Mexico for a 2-day incubation experiment, and bacteria that incorporated the peptide were identified using DNA stable isotope probing (SIP). The decomposition rate of AVFA in the bottom hypoxic seawater (0.018–0.035 μM h-1) was twice as fast as that in the surface normoxic seawater (0.011–0.017 μM h-1). SIP experiments indicated that incorporation of 13C was highest among the Flavobacteria, Sphingobacteria, Alphaproteobacteria, Acidimicrobiia, Verrucomicrobiae, Cyanobacteria, and Actinobacteria in surface waters. In contrast, highest 13C-enrichment was mainly observed in several Alphaproteobacteria (Thalassococcus, Rhodobacteraceae, Ruegeria) and Gammaproteobacteria genera (Colwellia, Balneatrix, Thalassomonas) in the bottom water. These data suggest that a more diverse group of both oligotrophic and copiotrophic bacteria may be involved in metabolizing labile organic matter such as peptides in normoxic coastal waters, and several copiotrophic genera belonging to Alphaproteobacteria and Gammaproteobacteria and known to be widely distributed may contribute to faster peptide decomposition in the hypoxic waters.